PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN BERBANTUAN VIDEO PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR SISWA SMP KATOLIK PALU: The Implementation Of Discovery Learning Model With The Assistance Of Video Learning On Spatial Structures Material To Improve Learning Outcomes Of Eight Grade Students In Palu City - Lumi, Jesica; Idris, Mustamin; Pathuddin; Rizal, Muh. (Universitas Tadulako, 2024)
This study aims to determine the improvement of student learning outcomes by using the Discovery Learning learning model assisted by learning videos on building material for grade VII students of Palu Catholic Junior High School. This research is Classroom Action Research using a quantitative & quality approach. The subjects of this study were class VIIIA students totaling 23 students consisting of 13 male students and 10 female students with diverse abilities. This research was carried out in two cycles. The application of the Discovery Learning learning model with the help of learning videos that can improve the learning outcomes of grade students of Palu Catholic Junior High School. This is shown from the completeness of individual students in the first cycle as many as 17 out of 23 students with a class average score of 79.34 and a classical percentage of 73.91%, who took the test increased to 20 out of 23 students with a class average score of 90.21 and the classical percentage is 86.95%, who took the test in cycle II, so that the success indicators set have been achieved and have reached the KKM standard that has been set at Palu Catholic Junior High School, which is 80.